35a Biennale Internazionale d'Arte. - Apollonio, Umbro; 35e Biennale di Venezia, 1970 (Venezia : La Biennale di Venezia, 1970)
Andreev, Nicolai ; Apostu, Gheorghe ; Arakawa, Shusaku ; Argov, Michael ; Augsburger, Jean-Edouard ; Battaglia, Carlo ; Benedit, Luis Fernando ; Bergallo, Armando ; Bernik, Janez ; Berriobena, Ignacio ; Bogart, Bram ; Bonalumi, Agostino ; Buic, Jagoda ; Carrino, Nicola ; Chirnoaga, Marcel ; Cruz-Diez, Carlos ; Dejneka, Alexandr ; Dzamonja, Duzan ; Fischer, Egon ; Frohner, Adolf ; Graatsma, William ; Hasior, Wladyslaw ; Haukeland, Arnold ; Hernandez, Francisco ; Ioannou, Georges ; Jacobi, Ritzi-Victoria ; Jankovic, Jozef ; Kolar, Jiri ; Laenen, Jean-Paul ; Leblanc, Walter ; Lenk, Kaspar Thomas ; Linnovaara, Juhani ; Lombardo, Sergio ; Mack, Heinz ; Malich, Karel ; Marx, Roberto Burle ; Mochetti, Maurizio ; Moswitzer, Gerhardt ; Paolini, Giulio ; Papadakis, Yannis ; Parent, Claude ; Parmakelis, Yannis ; Pfahler, Georg Karl ; Raba, Manuel Gomez ; Salisteanu, Ion ; Sekine, Nobuo ; Shavit, Amihai ; Slothauber, Jan ; Smith, Richard ; Snow, Michael ; Stämpfli, Peter ; Szajna, Jozef ; Uecker, Günther ; Verheyen, Jozef ; Verna, Claudio ; Vieira, Mary ; Vila, Ernesto ; Vilche, Hector ; Villalba, Darío ; Virilio, Paul ; Voegeli, Walter ; Wolf, Karl Anton ; Zarfati, Ruth ; Zerva, Eleni
35a Biennale Internazionale d'Arte, Venezia, 22.06 - 03.07.1970
Italiaans
kunstcatalogus